Micromachining‐Compatible, Facile Fabrication of Polymer Nanocomposite Spin Crossover Actuators. (22nd May 2018) - Manrique‐Juárez, María D.; Mathieu, Fabrice; Laborde, Adrian; Rat, Sylvain; Shalabaeva, Victoria; Demont, Philippe; Thomas, Olivier; Salmon, Lionel; Leichle, Thierry; Nicu, Liviu; Molnár, Gábor; Bousseksou, Azzedine
Abstract: [Fe II (Htrz)2 (trz)](BF4 ) spin crossover particles of 85 nm mean size are dispersed in an SU‐8 polymer matrix and spray‐coated onto silicon microcantilevers. The subsequent photothermal treatment of the polymer resist leads to micrometer thick, smooth, and homogeneous coatings, which exhibit well‐reproducible actuation upon the thermally induced spin transition. The actuation amplitude as a function of temperature is accurately determined by combining integrated piezoresistive detection with external optical interferometry, which allows for the assessment of the associated actuation force (9.4 mN), stress (28 MPa), strain (1.0%), and work density (140 mJ cm −3 ) through a stratified beam model. The dynamical mechanical characterization of the films evidences an increase of the resonance frequency and a concomitant decrease of the damping in the high‐temperature phase, which arises due to a combined effect of the thickness and mechanical property changes. The spray‐coating approach is also successfully extended to scale up the actuators for the centimeter range on a polymer substrate providing perspectives for biomimetic soft actuators. Abstract : The possibility of harnessing useful work from bistable molecules has inspired many scientists. Yet, their integration into functional systems remains in its infancy. Here, spray coating is proposed as a versatile and precise method for integrating "reluctant" molecular spin crossover materials as polymer composites into actuators. These biomimetic devices display large deflections, high work density, and perceptible color changes.